Analisis Perilaku Sanitasi Wisatawan terhadap penggunaan air Bersih dan Toilet di Kawasan Khusus Ekonomi Mandalika - Dujana, Lalu Muhammad Aby; Isrowati, Isrowati; Ahyadi, Hilman; Ernawati, Ernawati; Fadila, Baiq Arlina; Rahayu, Rachmawati Noviana; Rohyani, Immy Suci (LPPM Universitas Mataram, 2025)
The Mandalika Special Economic Zone (KEK) is a super priority destination in NTB with an increasing number of tourists visits every year. The increasing number of tourist visits affects the sanitation of the area. Sanitation conditions are influenced by tourist behavior. This study aims to analyze the sanitation behavior of tourists, especially in the use of clean water and toilets. The research method uses a questionnaire distribution to 96 tourists taken by simple random sampling. Determination of the number of respondents using the Slovin formula. The validity and reliability test of the questionnaire instrument was carried out first before the data was analyzed descriptively. The results of the study showed that 61% of respondents who had clean water use behavior in the Mandalika KEK had water use behavior in the